Pembrolizumab-Induced Thyroiditis Shows PD-L1Expressing Histiocytes and Infiltrating T Cells in Thyroid Tissue - A Case Report - Jabkowski, Jörg; Loidl, Almute; Auinger, Barbara; Kehrer, Helmut; Sepp, Norbert; Pichler, Robert (Frontiers in Immunology, 2021)
Context: Immune-related adverse events frequently take place after initiation of immune checkpoint inhibitors (ICI) therapy. The thyroid gland is the endocrine organ most commonly affected by ICI therapy, the pathomechanisms still being partially unrevealed. Case description: A 60-year old Upper Austrian male melanoma patient under pembrolizumab therapy received thyroidectomy because of a suspicious FDG avid thyroid nodule. Histopathology showed a pattern comparable with thyroiditis de Quervain. The inflammatory process consisted predominantly of T lymphocytes with a dominance of CD4+ T helper cells. Additionally CD68+ histiocytes were observed in clusters, them co-expressing PD-L1. Conclusion: Clusters of perifollicular histiocytes expressing PD-L1 were observed in this case of pembrolizumab induced thyroiditis - probably induced by the former ICI therapy. This finding might indicate the initial target for the breakdown of self tolerance. In context with other data the immunological process seems to be driven by CD3+ lymphocytes infiltrating the thyroid.